2020
DOI: 10.3390/ijerph17176040
|View full text |Cite
|
Sign up to set email alerts
|

Power, Muscle, and Take-Off Asymmetry in Young Soccer Players

Abstract: (1) Background: The objective of the study was to check the relationship between laterality, amount of muscle mass (MM), and selected strength parameters on lower extremities and assessment of asymmetry like a result of training. (2) Methods: The screened sample consisted of soccer players (n = 65, age = 16.0 ± 1.2 years). The legs were assessed for MM, height of reflection on a force plate, and power over 30 s Wingate anaerobic test (WAnT). The relationships between the individual parameters and age dependenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 41 publications
0
8
0
1
Order By: Relevance
“…Comparing the predictors of P peak and rP peak, it was observed that different anthropometric and F-v characteristics played a predicting role in each case. The best predictor of P peak was body mass highlighting the relationship of muscle power with human size ( Bahenský et al, 2020 ; Taketomi et al, 2021 ). Previously, it was shown that rP peak was related with 5 m, 30 m sprint times, maximal voluntary isometric contraction of the knee extensors, half squat repetition maximal and countermovement jump height in soccer players ( Boraczyński et al, 2020 ), performance of short and maximal effort that might be evaluated by the F-v test.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparing the predictors of P peak and rP peak, it was observed that different anthropometric and F-v characteristics played a predicting role in each case. The best predictor of P peak was body mass highlighting the relationship of muscle power with human size ( Bahenský et al, 2020 ; Taketomi et al, 2021 ). Previously, it was shown that rP peak was related with 5 m, 30 m sprint times, maximal voluntary isometric contraction of the knee extensors, half squat repetition maximal and countermovement jump height in soccer players ( Boraczyński et al, 2020 ), performance of short and maximal effort that might be evaluated by the F-v test.…”
Section: Discussionmentioning
confidence: 99%
“…Performance in soccer has been shown to rely on movements such as sprinting, passing, shooting, jumping, and change of direction ( Lepschy et al, 2021 ; Longo et al, 2021 ). Considering the short duration and maximal effort characterizing these movements, it was not surprising that the Wingate anaerobic test (WAnT), an all-out 30-s test on a cycle ergometer, was widely used to evaluate performance in this team sport ( Chtourou et al, 2019 ; Bahenský et al, 2020 ). The most popular index of the WAnT has been the peak power expressed either in absolute (Ppeak) or relative to body mass values (rPpeak).…”
Section: Introductionmentioning
confidence: 99%
“…Identifying the differences in characteristics between DLs and NDLs in soccer players may help to elucidate how leg dominance and musculoskeletal asymmetry are related to injury risk and improve injury prevention. Although there have been several reports on the differences in characteristics of DL and NDL in soccer [18][19][20], the data are not sufficient. There are few systematic and comprehensive studies comparing DL and NDL including anthropometries [21], muscle strength, balance ability, joint range of motion, and muscle flexibility, whereas most have focused on limited factors such as muscle strength [17,22] or neuromuscular control [23], or on a single joint such as the hip joint [19].…”
Section: Introductionmentioning
confidence: 94%
“…Neexistuje ale souvislost mezi silou DK při WAnT a množství SH při hodnocení obou jednotlivých končetin společně. To je v souladu se závěry při hodnocení 30s testu (Bahenský, Marko, Bunc, & Tlustý, 2020). Souvislost také nebyla nalezena mezi úrovní odrazové síly a množství SH na DK.…”
Section: Diskuzeunclassified